Optical coherence tomography in acute optic neuritis: A population‐based study. (14th August 2018) - Soelberg, Kerstin; Specovius, Svenja; Zimmermann, Hanna G.; Grauslund, Jakob; Mehlsen, Jesper J.; Olesen, Clement; Neve, Allan S. B.; Paul, Friedemann; Brandt, Alexander U.; Asgari, Nasrin
Abstract : Objectives: To measure early structural damage caused by autoimmune inflammatory optic neuritis (ON) by optical coherence tomography (OCT) in a population‐based cohort. Methods: In a prospective population‐based study over 24 months in Southern Denmark, patients diagnosed with acute ON and without prior diagnosis of a chronic neuroinflammatory disorder were included and examined with OCT, visual evoked potentials (VEP), visual fields, high contrast visual acuity (HCVA), and low contrast letter acuity (LCLA). Structural and functional outcomes were determined at 6‐month follow‐up based on interocular differences. Results: The 50 included patients had on average 16.9 μm peripapillary retinal nerve fiber layer loss, 10.6 μm ganglion cell and inner plexiform layer (GCIP) loss, and an average HCVA decrease of 0.22 dec. Based on a linear regression model, average GCIP loss amounted to −0.2 μm per day and started 8 days after onset. OCT outcomes but not VEP correlated well with all visual function measurements at follow‐up. Structural and functional damage in 20 patients (40%) diagnosed de novo with multiple sclerosis (MS) and in 2 patients (4%) with positive myelin oligodendrocyte glycoprotein antibodies (MOG‐IgG) test did not differ from patients with idiopathic ON. Conclusions: Optic neuritis causes substantial retinal damage and vision loss independent of the underlying disease. Our study supports that GCIP damage starts closely to clinical onset. Good structure‐function correlations between OCT and vision support the importance of OCT in monitoring acute ON.